Empagliflozin attenuates neurodegeneration through antioxidant, anti-inflammatory, and modulation of α-synuclein and Parkin levels in rotenone-induced Parkinson's disease in rats - Sanaa Ahmed; Mahmoud M. El-Sayed; Mohamed A. Kandeil; Marwa M. Khalaf (Elsevier, 2022)
Sodium-glucose co-transporter 2 (SGLT 2) inhibitors are a relatively new antidiabetic drug with antioxidant and anti-inflammatory properties. Therefore, this study aimed to investigate whether SGLT 2 inhibitors have a neuroprotective effect in PD. Twenty-four Wistar rats were randomized into four groups. The first one (control group) received dimethyl sulfoxide (DMSO) as a vehicle (0.2 mL/48 hr, S.C). The second group (positive control) received rotenone (ROT) (2.5 mg/kg/48 hr, S.C) for 20 successive days, whereas the third and fourth groups received empagliflozin (EMP) (1 and 2 mg/kg/day, orally), respectively. The two groups received rotenone (2.5 mg/kg/48 hr S.C) concomitantly with EMP for another 20 days on the fifth day. By the end of the experimental period, behavioral examinations were done. Subsequently, rats were sacrificed, blood samples and brain tissues were collected for analysis. ROT significantly elevated oxidative stress and proinflammatory markers as well as α-synuclein. However, dopamine (DP), antioxidants, tyrosine hydroxylase (TH), and Parkin were significantly decreased. Groups of (EMP + ROT) significantly maintained oxidative stress and inflammatory markers elevation, maintained α-synuclein and Parkin levels, and elevated TH activity and dopamine level. In both low and high doses, EMP produced a neuroprotective effect against the PD rat model, with the high dose inducing a more significant effect.